SUITABILITY OF 25 LOCALLY SELECTED SUGARCANE GENOTYPES (SACCHARUM SPP.) FOR USE AS DIFFERENTIALS IN SMUT [USTILAGO SCITAMINEA (SYD.)] RACE TYPING IN THE SUDAN - -d, Marchelo; *, Ragga; *, P.W. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Studies were conducted at Sugarcane Research Centre, Guneid, (Latitude 15o N, longitude 33o E) for three consecutive seasons namely, 2006/2007; 2007/2008 and 2008/2009. The objectives were to test 25 locally selected sugarcane genotypes for suitability and use as differentials in race typing of Ustilago scitaminea (Syd.) the causal agent of sugarcane smut disease. Six smut isolates from different sugarcane growing areas of Sudan namely, Guneid: (GN1), (GN2) and (GN3); Sennar: (SN); New Halfa: (NH) and AB from Abbasiya (Assalaya/ Kenana area) were tested. Test materials were inoculated by three methods of: pin-prick method (PPM); Dipping method (DM) and Natural spreader row infection methods (NIM), respectively. Results showed the presence of four races of Ustilago scitaminea (Syd.) in Sudanese sugarcane fields that have relatedness percentages of 60-80% to each other. Hence, there is no virulent race of U. scitaminea (Syd.) at this time in the country and, the occurrence of infections on the popular varieties is normal and does not signal any danger of an epiphytotic. Therefore, the study recommends the adoption of the 25 genotypes as suitable differentials for smut race typing, continuation of current agricultural practices and the re-examination of U. scitaminea (Syd.) race status within the next ten years.